Dari Rumah ke Sekolah: Keterlibatan Orang Tua dalam Asesmen Perkembangan Anak - Anawaty, Mardiyana Faridhatul; Nisa, Titin Faridatun; Syafitri, Ima Cahyani (JEA (Jurnal Edukasi AUD), 2024)
Assessment activities are carried out to determine the achievement of child development. Assessment activities involve teachers and parents. This study examines parental involvement in assessments by the principles of assessment, namely parents as a source of assessment information and as listeners. This study involved 81 parents with early childhood children attending the Penggerak Kindergarten institution in Bangkalan District. Data collection techniques used questionnaires, interviews, and documentation. The results of the study showed that parents tend to be able to carry out their roles by one of the principles of assessment, namely as a source of information by providing information about the strengths and weaknesses of children and parents can be listeners to information on child development delivered by teachers. This study provides new insights into the role of parents in early childhood development assessments. This study contributes to education to be able to involve parents not only in learning activities but also in child development assessments.